Promote Replica Management based on Data Mining Techniques - M. Almuttairi, Rafah; S. Almhanna, Mahdi; Q. Mohammed, Mohammed; Q Muhamed, Saif (International Journal of Engineering and Technology, 2018)
The data grid technique evolved largely in sharing the data in multiple geographical stations across different sites to improve the data access and increases the speed of transmission  data. The performance and the availability of the resources is taken into account, when a total of sites holding a copy of files, there is a considerable benefit in selecting the best set of replica sites to be cooperated for increasing data transfer job. In this paper, new selecrtion strategy is proposed to reduce the total transfer time of required files. Pincer-Search algorithm is used to explore the common characteristics of sites to select uncongested  replica sites.